Changes in some female reproductive parameters of Albino wistar rats by hydroethanol leaf extract of fleurya aestuans - F. S., Amah-Taria; C. C., Nwafor; A. A., Ajah; M. T., Bekinbo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: This study investigated the effects of hydro-ethanolic leaf extract of Fleurya aestuans (FA) on some female reproductive hormones in female albino wistar rats. Methods: Thirty-two (32) rats weighing 120 to 200g were grouped into four of eight rats each. After two weeks of acclimatization, group 1 served as the control group. Groups 2, 3 and 4 served as the test groups and were orally administered with (75, 150 and 300) mg/kg body weight of hydro-ethanolic leaf extract of Fleurya aestuans (FA) respectively, for 42 days. The animals were allowed access to water and feeds ad libitum. At the end of treatment, the animals were properly sedated and blood samples were collected via cardiac puncture. The blood samples were centrifuged and serum obtained was used to determine the concentrations of follicle stimulating hormone (FSH), luteinizing hormone (LH), estrogen and progesterone using the ELISA method. Also, the ovaries of each rat were harvested and fixed for histological studies. Raw data were analyzed using SPSS version 20.0. Results: The hydro-ethanolic leaf extract of F. aestuans significantly (P<0.05) increased serum concentrations of FSH and LH in all test groups. Whereas, estrogen and progesterone increased significantly (P<0.05) in test Groups 2 (75mg/kg) and 3 (150mg/kg) but were significantly (P<0.05) decreased in test Group 4 (300mg/kg). Histological examination of the ovaries showed only primary follicles in Groups 1 and 4, while, Graafian follicle and corpus luteum were seen in groups 2 and 3. This suggests that the hydro-ethanolic leaf extract of Fleurya aestuans contains possible biologically active properties that may be potent in enhancing serum concentrations of FSH, LH, estrogen and progesterone but may be ineffective at a higher dose. Conclusions: The current study showed that hydro-ethanolic leaf extract of Fleurya aestuans promotes fertility in females and suggests that caution be taken in the quantity of this extract consumed if to be considered for fertility enhancement purposes in females.